Rock bolt and frame support of mine workings with a compound cross-section: Collective refuge chambers for mine workers - Krukovskyi, Oleksandr; Krukovska, Viktoriia; Bulich, Yurii; Demchenko, Serhii; Konstantynova, Iryna (Mining of Mineral Deposits, 2024)
Purpose is to study the influence of mining and geological conditions on the time-dependent stability of the collective refuge chamber for mine workers with the adjacent mine workings and develop support schemes for different conditions of construction of such mine workings. Methods. Numerical modelling methods of the connected processes of elastoplastic deformation of gas-bearing rocks and gas filtration within the area disturbed during mining operations were used to study stability of mine workings with a compound cross-section, i.e. the collective refuge chambers and its adjacent extraction gallery. The model was based on fundamental principles of solid mechanics and filtration theory. The problem was solved using a finite element method. Findings. A classification of the conditions for locating collective refuge chambers for mine workers according to the relative strength of the enclosing rocks was developed. Support schemes for the chamber and its adjacent mine working were elaborated. The schemes include basic support and provide for its strengthening with rock bolts located in the roof of the mine working and chamber, or in their walls. The compliance of these support schemes with the developed classification of location conditions was determined. A numerical study of the time-dependent stability of the chamber and its adjacent mine working, while applying the recommended support scheme, was performed. It is shown that the strengthening of rock bolting schemes reduces the multicomponent stress field and the area of the zone of inelastic deformations, forms a rock-bolt overlap in the roof of the mine workings and chambers, which helps increase their stability under the complicated mining and geological conditions. Originality. Dependence of the changes within the area of a zone of inelastic deformations around the chamber with its adjacent mine working on the relative strength of the enclosing rocks was identified; time-dependent changes within the area of the zone of inelastic deformations, when using different support types, were specified. Practical implications. Support schemes for collective rescue chambers for mine workers in terms of different construction conditions were developed along with the procedure of their selection for specific mining and geological conditions. The results of the study provide theoretical substantiation and scientific guidelines for the selection of supports for collective refuge chambers adjacent to the mine working.